AN ANALYSIS OF THE STRUCTURE OF ROMANIAN MONETARY MASS - OANA DOBRE-BARON (Annals of the University of Petrosani: Economics)
The analysis of the structure and evolution of the different parts of monetary mass is subordinated to designing future monetary policy. Sizing the monetary mass and following its evolution, of the different tendencies registered by its component assets with different degrees of liquidity, is accomplished using certain monetary indicators integrated into a monetary analysis model capable of explaining and orienting the processes and monetary policy. This is the prerogative of the monetary authority of every nation. In Romania this authority is the Romanian National Bank (BNR). This study seeks to dynamically analyse the monetary mass of Romania between 2013-2017, the categoris of indicators in which it is structured, as well as monetary assets with different degrees of liquidity which are included in different monetary aggregates.